Enhancing Financial Management in Education by Strengthening Training, Staff Competency, and Organizational Support in Indonesia - Warizal (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Effective financial management is increasingly vital for educational institutions as they face complex reporting standards, growing accountability demands, and the need to align with global practices. In this context, the competency of financial staff and the quality of training programs are central to ensuring transparency and institutional sustainability. This study aims to examine the relationship between training, staff competency, and financial reporting quality, while also exploring contextual factors that influence financial management effectiveness in Indonesian educational institutions. A sequential explanatory mixed-methods design was employed. The quantitative phase involved survey data from 200 financial personnel to identify statistical relationships among training, competency, and reporting quality. This was followed by qualitative interviews with 15 participants to capture deeper insights into organizational and cultural dynamics shaping these relationships. The results indicate a significant positive correlation between training quality and staff competency (r = 0.728, p < 0.001), and between competency and financial reporting quality (r = 0.473, p < 0.001). The findings emphasize the importance of leadership, organizational culture, and technology in implementing competencies through a holistic approach encompassing training, development, and a supportive environment for excellence in educational financial management.